HOMESCHOOLING PADA ANAK USIA DINI DALAM PERSPEKTIF PENDIDIKAN ISLAM BERBASIS MULTIDISIPLINIER, INTERDISIPLINEAR DAN TRANSDISIPLINEAR - Novita Harini; Syaifuddin Sabda; Husnul Yaqin; Ridhahani Fidzi (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2025)
This article aims to explore the concept of Homeschooling for early childhood in the perspective of Islamic education, integrated with multidisciplinarity, interdisciplinarity, and transdisciplinarity. Early childhood education is a crucial phase in the development of character, cognitive abilities, and social skills. Homeschooling, as an alternative form of education outside the formal system, provides space for the implementation of more flexible education that is tailored to the individual needs of children. In the context of Islamic education, Homeschooling is seen as a method that allows for the instillation of religious values, ethics, and morals from an early age, serving as a foundation for the intellectual and spiritual development of children. The multidimensional approach in this study integrates various disciplines, such as psychology, pedagogy, and sociology, to understand the dynamics of child development within the Homeschooling environment. The interdisciplinary approach brings together concepts from various fields, such as Islamic theology, philosophy of education, and child education sciences, which synergistically enrich Homeschooling practices within the context of Islamic education. Meanwhile, the transdisciplinary approach emphasizes openness and collaboration between different disciplines to create a holistic understanding of implementing Homeschooling based on Islamic values. Homeschooling for early childhood in the perspective of Islamic education, supported by multidisciplinarity, interdisciplinarity, and transdisciplinarity, can make a significant contribution to the formation of morally upright, intelligent children with strong personalities. This educational model offers the potential to create a more personalized learning environment that aligns with Islamic principles, fostering a balance between the worldly and spiritual aspects of a child. Furthermore, the application of these principles can enrich the Homeschooling method with a more comprehensive and adaptive approach to the needs of contemporary society.